Influence of the finite Q-factor on excitation of wakefield oscillations in dielectric cavity by a sequence of relativistic electron bunches in the presence of detuning between the resonant frequency and the bunch repetition frequency - Balakirev, V.A.; Onishchenko, I.N.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2015)
Excitation of Cerenkov wakefield oscillations in dielectric cavity with finite value of Q-factor in the presence of detuning between the bunch repetition frequency and the resonant frequency of the excited oscillations is investigated. It is shown that the picture of wake oscillations excitation is determined by the ratio between the value of the Q-factor and frequency detuning parameter πω/δω. For the high Q-factor dielectric cavity Q >>πω/δω picture of wake oscillations excitation is the same as in the cavity without ohmic losses. If the opposite condition is satisfied, the process of wakefield excitation occurs almost as well as in the case of resonant excitation. Linear growth of the wakefield amplitude at initial stage reaches its saturation level. Изучен процесс возбуждения кильватерных колебаний в диэлектрическом резонаторе с конечным значением добротности Q при наличии расстройки между частотой следования сгустков и частотой резонансного колебания. Показано, что картина возбуждения кильватерных колебаний определяется соотношением между значением добротности Q и параметром частотной расстройки πω/δω. В случае высокой добротности диэлектрического резонатора Q >>πω/δω картина возбуждения кильватерных колебаний такая же, как и в резонаторе без омических потерь. В диэлектрическом резонаторе формируется биение кильватерного поля. Если выполнено противоположное условие, картина возбуждения кильватерных колебаний практически не отличается от случая резонансного возбуждения. После начального линейного роста амплитуды имеет место ее насыщение на постоянном уровне. Вивчено процес збудження кільватерних коливань у діелектричному резонаторі із скінченним значенням добротності Q при наявності розстройки між частотою проходження згустків і частотою резонансного коливання. Показано, що картина збудження кільватерних коливань визначається співвідношенням між значенням добротності Q й параметром частотної розстройки πω/δω. У випадку високої добротності діелектричного резонатора Q >>πω/δω картина збудження кільватерних коливань така ж, як і в резонаторі без омічних втрат. У діелектричному резонаторі формується биття кільватерного поля. Якщо виконана протилежна умова, картина збудження кільватерних коливань практично не відрізняється від випадку резонансного збудження. Після початкового лінійного росту амплітуди має місце її насичення на постійному рівні.